2016
DOI: 10.3748/wjg.v22.i24.5548
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive risk assessment for early neurologic complications after liver transplantation

Abstract: NCs post- liver transplantation occurs because of factors related to recipient, donor, and surgeon. Our results provide a basis of risk stratification for surgeon to minimize neurotoxic factors during transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
6
7
0
1
Order By: Relevance
“…Hypothetically, it may be related to a lower capacity of older livers of metabolizing such drugs. Lue et al's results could be partially in line with those described by Wu et al, who reported that donor age <22 or ≥40 years and graft-recipient weight ratio are associated with neurological complications after LT (9). In this study, that included 295 adult LT recipients (193 of whom received their grafts from living donors), the incidence of neurological complications was 49.3%, with encephalopathy being the most common complication (n=106, 73%).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Hypothetically, it may be related to a lower capacity of older livers of metabolizing such drugs. Lue et al's results could be partially in line with those described by Wu et al, who reported that donor age <22 or ≥40 years and graft-recipient weight ratio are associated with neurological complications after LT (9). In this study, that included 295 adult LT recipients (193 of whom received their grafts from living donors), the incidence of neurological complications was 49.3%, with encephalopathy being the most common complication (n=106, 73%).…”
supporting
confidence: 88%
“…In addition, Yamauchi et al described that a polymorphism in the ABCB1 gene may be a risk factor for tacrolimus induced neurotoxicity in related living donor LT recipients (7). However, few studies have evaluated donor and technical aspects as potential risk factors for CNI-neurotoxicity in liver transplant recipients (8,9).…”
mentioning
confidence: 99%
“…Conditions that increase the neurotoxicity of immunosuppressant agents include pre-existing mental disorders [78], hypertension [79], electrolyte disorders including hyper and hyponatremia and hypomagnesemia [37], dysmetabolic alterations, such as hyperglycemia [37], infections that impair the function of the blood–brain barrier (BBB), hypocholesterolemia, which increases the uptake of immunosuppressant drugs in the brain [80], polymorphisms of the adenosine triphosphate (ATP)-binding cassette transporter B1 (ABCB1) gene and cytochrome pigment (CYP) gene, which decrease immunosuppressant efflux or elimination [81,82], drug interactions [82,83], a prolonged surgical period [84], and low liver function or acute liver failure [85].…”
Section: Clinical Features Induced By Different Immunosuppressantsmentioning
confidence: 99%
“…Conditions that increase the neurotoxicity of immunosuppressant agents include pre-existing mental disorders [78]; hypertension [79]; electrolyte disorders, including hyper-and hyponatremia and hypomagnesemia [37]; dysmetabolic alterations, such as hyperglycaemia [37]; infections that impair the function of the blood-brain barrier (BBB); hypocholesterolaemia, which increases the uptake of immunosuppressant drugs in the brain [80]; polymorphisms of the ATP-binding cassette transporter B1 (ABCB1) gene and cytochrome pigment (CYP) gene, which decrease immunosuppressant efflux or elimination [81,82]; drug interactions [82,83]; a prolonged surgical period [84]; and low liver function or acute liver failure [85].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%